Peculiarity of translation of attribute groups from English into Ukrainian (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The grammatical and semantic factors influencing on the translation of English attribute groups into Ukrainian are determined. English attribute lexeme can be translated by one word, word-combination or relative clause. It is necessary to begin translating from analysing semantic connections between the components of the word-combination.
Keywords: translation; attribute word-combination; lexical-grammatical transformation